Immunology of cord blood T-cells favors augmented disease response during clinical pediatric stem cell transplantation for acute leukemia - Borrill, Roisin; Poulton, Kay; Wynn, Robert (Frontiers in Pediatrics, 2023)
This review focuses on cord blood transplantation for acute leukemia, synthesizing clinical, biological, and immunological aspects. We review recent research into clinical cord blood transplantation, focusing on superior outcomes for high-risk leukemia compared to conventional stem cell sources, due to reduced rates of relapse. We also describe the challenges faced with cord blood transplantation, including infection and graft-versus-host disease and future work that may be helpful in overcoming them. We link these clinical attributes with a discussion on the immunology of cord blood and immune reconstitution following stem cell transplantation. The key differences between cord blood and peripheral blood are highlighted, with a particular focus on T-cells, which are important mediators of antitumor activity. Importantly this review describes future directions in cord blood transplantation, including research into better understanding of the graft-versus-leukemia effect and new methods to augment and refine the immunological characteristics we have discussed. This review is important and relevant, as research in this area is rapidly progressing with new techniques to maximize the potential of cord blood.